An Unprecedented Kernel Growth Mode and Layer‐Number‐Odevity‐Dependent Properties in Gold Nanoclusters. (18th November 2019) - Liao, Lingwen; Wang, Chengming; Zhuang, Shengli; Yan, Nan; Zhao, Yan; Yang, Ying; Li, Jin; Deng, Haiteng; Wu, Zhikun
Abstract: Kernel atoms of Au nanoclusters are packed layer‐by‐layer along the [001] direction with every full (001) monolayer composed of 8 Au atoms (Au8 unit) in nanoclusters with formula of Au8n+4 (TBBT)4n+8 (n is the number of Au8 units; TBBTH=4‐tert‐butylbenzenelthiol). It is unclear whether the kernel atoms can be stacked in a defective‐layer way along the [001] direction during growth of the series of nanoclusters and how the kernel layer number affects properties. Now, a nanocluster is synthesized that is precisely characterized by mass spectrometry and single‐crystal X‐ray crystallography, revealing a layer stacking mode in which a half monolayer composed of 4 atoms (Au4 unit) is stacked on the full monolayer along the [001] direction. The size and the odevity of the kernel layer number influence the properties (polarity, photoluminescence) of gold nanoclusters. The obtained nanocluster extends the previous formula from Au8n+4 (TBBT)4n+8 to Au4n+4 (TBBT)2n+8 (n is the number of Au4 units). Abstract : Tanzt aus der Reihe : Der Nanocluster Au56 (TBBT)34 wurde synthetisiert. Röntgenkristallographie zeigt einen fehlerhaften Kernschicht‐Stapelmodus, der sich von der magischen Reihe von Nanoclustern, Au28 (TBBT)20, Au36 (TBBT)24, Au44 (TBBT)28, Au52 (TBBT)32 und Au56 (TBBT)34, unterscheidet. Nicht nur die Größe, sondern auch die Parität der Kernschichtzahl beeinflusst die Polarität und Photolumineszenz des Metall‐Nanoclusters.